PENGARUH CONTENT CREATOR DAN PROMOSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DAN DIMODERASI OLEH TRUST PADA APLIKASI TIKTOK SHOP DI MAHASISWA FE UNISRI - Aprian Aditama, Rizky Ramadhan; Anna Probowati; Dewi Shanti Nugrahani (JURNAL ILMIAH EDUNOMIKA, 2025)
The advancement of digital technology has transformed consumer shopping behavior, where the presence of Content Creators and price promotion strategies play a crucial role in influencing purchasing decisions on e-commerce platforms such as TikTok Shop. This study aims to analyze the influence of Content Creators and price promotions on purchasing decisions, with trust as a moderating variable. A quantitative research approach was employed, utilizing Partial Least Square - Structural Equation Modeling (PLS-SEM) for data analysis on 175 respondents, consisting of students from the Faculty of Economics at Slamet Riyadi University, Surakarta. The findings indicate that both Content Creators and price promotions have a positive and significant impact on purchasing decisions. Furthermore, trust serves as a moderating variable that strengthens the relationship between Content Creators and purchasing decisions. The implications of this study suggest that marketers should optimize digital marketing strategies by selecting credible Content Creators and fostering consumer trust to enhance sales conversions on TikTok Shop. Keywords : Content Creator, Price Promotion, Trust, Purchasing Decision, TikTok Shop